2001
DOI: 10.1191/026921601678576239
|View full text |Cite
|
Sign up to set email alerts
|

Use of clinical pictures in the management of nausea and vomiting: a prospective audit

Abstract: This prospective audit aimed to evaluate a guideline for the management of nausea and vomiting in palliative care inpatients. Clinical pictures were used to guide diagnosis and treatment, with potentially reversible causes being addressed where appropriate. Over a 3-month period, 40 patient episodes occurred, all of which were included in the audit. The commonest clinical pictures were gastric stasis/outlet obstruction (35%) and chemical/metabolic (30%). Management according to the guideline was effective. Nau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 5 publications
2
38
0
3
Order By: Relevance
“…Experts in the field claim that the cause of nausea and vomiting can be determined clinically in 90% cases [8,9], although they recognize that the cause is usually multifactorial. It is claimed that more than 80% of patients can have their nausea and vomiting controlled when treated in this way [8,10]. The evidence upon which this claim is made warrants review.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experts in the field claim that the cause of nausea and vomiting can be determined clinically in 90% cases [8,9], although they recognize that the cause is usually multifactorial. It is claimed that more than 80% of patients can have their nausea and vomiting controlled when treated in this way [8,10]. The evidence upon which this claim is made warrants review.…”
mentioning
confidence: 99%
“…Antiemetic choice is based on identifying the likely mechanism of the symptoms from the clinical picture and applying knowledge of the neuropharmacology of the emetic pathway [6,7]. Experts in the field claim that the cause of nausea and vomiting can be determined clinically in 90% cases [8,9], although they recognize that the cause is usually multifactorial. It is claimed that more than 80% of patients can have their nausea and vomiting controlled when treated in this way [8,10].…”
mentioning
confidence: 99%
“…B. Schmerz, Übelkeit, Erbrechen, Agitation, Dyspnoe), der Umgang mit Krisensituationen sowie ethische Fragestellungen beispielsweise bezüglich Therapieindikation bzw. -reduktion sind in unterschiedlichen Bereichen der Anäs-thesiologie in der täglichen Routine gegeben [3,5,11,12,16,17,18,19,22,23,32]. Eine Übertragbarkeit anästhesiologisch-therapeutischer Optionen ist -allerdings mit zusätzlichen palliativmedizinischen Aspekten (beispielsweise Berücksichtigung psychosozialer und spiritueller Faktoren) -in der Palliativmedizin durchaus denkbar.…”
Section: Vergleich Der Weiterbildungsinhalte Anästhesiologischer Zusaunclassified
“…Die Anästhesiologie kann mit ihren einzelnen Subspezialisierungen und weitreichenden Erfahrungen in der Kooperation mit anderen Fachdisziplinen und Professionen für eine solche Therapiekoordination hilfreich sein [4,5,9,11,16,17,18,20,37]. Aufgrund der bereits bestehenden Vielseitigkeit des Faches und der breiten fachlichen Herausforderungen in der täglichen Klinikroutine sollte die Palliativmedizin für Anästhesisten als koordinierende Instanz keine unlösbare Aufgabe darstellen.…”
Section: Bedeutung Einer Anästhesiologischen Abteilung Für Die Palliaunclassified
“…Two prospective audits of current practice have showed response rates of 80%-90% when following this approach. 74,75 An alternative approach of empiric treatment has been recommended by some, and in studies was found to be highly effective. [76][77][78][79] There have been no head to head comparisons of these approaches.…”
Section: Managementmentioning
confidence: 99%